Mini Rice Harvester / Nor Shahidah Shaharun...[et.al] - Shaharun, Nor Shahidah; Abd Ghani, Nor Azreen; Yunus, Nur Hidayah; Abd Runi, Nor Syuhana; Salleh, Norshahira (Faculty of Plantation and Agrotechnology, 2017)
Technology today has made a much more direct impact to the end user. M-tech is the name that has been given to our company. M-tech is a company which has potential to be position as one a successful technology business throughout our creative innovation. This innovation had been implemented by foreign country such as Thailand and China but not yet in Malaysia. Therefore, we take this opportunity through come up with new mini rice harvester technology. This machine is a new invention in machinery which provides best machine for the retailer. With experience in farming machines researching and designing, it becomes a respected manufacturer in agricultural field. M-tech give opportunity to the small farmers by using high quality farm machines with cost effective price. Our company will acts as creator and the supplier of this product. This company is subdivided into 4 department which are administration, operation, marketing, and financial department. Due to that, M-tech is requiring workforce on technician to ensure those work run smoothly without excessive overhead. This additional workforces are composing of general worker where they will help the operation managers with particular works such as service and maintenance. We also hired a temporary engineer to give advice and designing the machine during the planning stage. We choose to involve the third party in order to manufacture the small rice harvester machine that specially designed by our company.